Rapid micropropagation of Begonia tuberous by young leaf tissue culture and acclimatization in greenhouse - Khiem, Dinh Van; Nhu Lan, Le Thi; Nhut, Duong Tan; Luong, Mai Xuan (Academia Journal of Biology, 2015)
In this paper, the protocol for the rapid micropropagation of Begonia tuberous are presented. The shoot regeneration was carried out on 1/2MS medium, plus 0.7 mg/l BA and 0.03 mg/l NAA. Furthermore, the callus formation was obtained on 1/2MS medium supplemented with 0.7 mg/l BA and 0.1 mg/l NAA. For the shoot multiplication, single shoots were cultured on MS medium, plus 1 mg/l BA and 0.3 mg/l NAA. The root formation was obtained on 1/2MS medium, plus 0.5 mg/l NAA and 0.3  mg/l IBA. To increase the growth and development possibility of Begonia tuberous in the greenhouse, we can use some chemical fertilizers (nitrophoska, Grow more, super) at a suitable dosage.